Persepsi terhadap Kemampuan Komunikasi Interpersonal Orang Tua dengan Kecenderungan Kenakalan Remaja - Fadiah Awanis; Maria Goretti Adiyanti (Gadjah Mada Journal of Psychology (GamaJoP), 2018)
This study aimed to determine the relationship between perception of parent’s interpersonal communication ability with juvenile delinquency tendency. The hypothesis of this study was the perception of parent’s interpersonal communication ability had a negative correlation with juvenile delinquency tendency. Participants consisted of 100 male and female middle adolescent who studied in several senior high schools in Yogyakarta. The Perception of Parent’s Interpersonal Communication Ability Scale (18 items) and The Tendency of Juvenile Delinquency Scale (25 items) were used in this study. Data were analyzed using the Product Moment Pearson Correlation method with SPSS version 21. The result showed that the perception of parent’s interpersonal communication ability had a negative correlation with juvenile delinquency tendency (r=-0,295, p<0,01). Findings support  the opposite relationship between how adolescents perceive the ability of parents' interpersonal relationships with their juvenile delinquency.